Consulta@mgf.pt: A case report of doctor-patient communication using e-mail - Botas, Philippe (2012)
consulta@mgf.pt:A CASE REPORT OF DOCTOR-PATIENT COMMUNICATION USING E-MAIL Introduction: New methods of communication, such as electronic mail, can complement the General practice/Family medicine consultation. The case: A 28 year old woman who rarely consulted with her family doctor was diagnosed with depression and low self-esteem in a consultation requested for other reasons. She had low family support and was found to be in crisis. The patient rejected the offer of drug treatment. The treatment proposed consisted of introspection-oriented work through written texts sent by email to her family doctor. Coping was enhanced with progressive resolution of the depressive symptoms noted over a four month period. Commentary: E-mail communication with the patient was found to promote adherence to treatment, patient empowerment, and the doctor-patient relationship. This met the patients needs in a timely way without extra work for the doctor.